Economic and political challenges af acceding to the euro zone area: The case of Poland - Przemysław Woźniak (Center for Social and Economic Research (CASE), 2010)
The paper examines economic and political challenges of joining the euro area in the case of Poland. After reviewing the economic developments since the pre-accession period and assessing economic convergence with the euro area the paper focuses on the political and institutional challenges of acceding to the euro zone. Special attention is given to the effect of the crisis triggered by the collapse of Lehman brothers in September 2008 on both political and economic dynamics of the process. The developments in parameters related to the economic and legal criteria for joining the euro area are scrutinized in detail during the entire period before and after the crisis. The paper is concluded with the review of the status quo in mid-2010 as well as summary and recommendations.
Keywords: E5; E6; F4; 330; Euro; area; enlargement; Poland; financial crisis; Eurozone; Eurozone; EU-Mitgliedschaft; Mitgliedschaft; Wirtschaftskrise; Polen